Determination of Total Phenolic Levels in Ethanol Extract of Moringa (Moringa oleifera L.) Leaves based on Differences in Growing Sites - Any Guntarti; Nining Sugihartini; Siti Athiyah Umaiyah; Nina Salamah (Journal of Food and Pharmaceutical Sciences, 2021)
Moringa oleifera L. have good nutritional content including phenolic compounds which can be used as antioxidants and can grow in lowlands and highlands. The purpose of this study was to determine the total phenolic content of the ethanol extract of M. oleifera leaves with variations in the area of ​​collection. The 50% ethanol extract was obtained from the simplicia of M. oleifera leaves by using the maceration method. Analysis of total phenolic content in the extract was carried out using a spectrophotometer instrument with the addition of reagent Folin-Ciocalteu and gallic acid as standard. The results of total phenolic content in Sleman, Wonosari, and Wonosobo areas were (127.87 ± 2.71) mg GAE / g extract, (99.40 ± 2.68) mg GAE / g extract, and (142 , 92 ± 1.81) mg GAE / g extract. The highest phenolic content in the ethanol extract of moringa leaves was found in Wonosobo areas.